A novel high-entropy alloy with a dendrite-composite microstructure and remarkable compression performance. (15th January 2019) - Fan, J.T.; Zhang, L.J.; Yu, P.F.; Zhang, M.D.; Li, G.; Liaw, P.K.; Liu, R.P.
Abstract: In the present study, a novel dendrite-composite high-entropy alloy consisting of nano-structured interdendritic regions and coarse dendrites was successfully designed and prepared by arc-melting. Interestingly, the as-cast Al18 Fe33.3 Co23 Ni23 C2.7 (at. %) alloy exhibited a great combination of high compressive strength and strain. More importantly, the new material exhibited pronounced three-stage work-hardening behavior. It was found that deformation twinning in the interdendritic region is the dominant mechanism responsible for the multi-stage work-hardening, thereby leading to good compression behavior of the new material. The synergistic effects between the dendrite and interdendritic regions are also effective for improving the mechanical property of the alloy. Graphical abstract: Unlabelled Image